PROPOSTA DE INSERÇÃO DE ESTRATÉGIAS BIOCLIMÁTICAS EM HABITAÇÕES AUTO CONSTRUÍDAS, COM O USO DA GRAMÁTICA DA FORMA - Loche, Iris Maria Costa Fajardo Werneck; Carlo, Joyce Correna; Fonseca, Ligiana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Facing a Brazilian scenario of housing deficit and failed social politics created for providing housings in a quantitative way and guaranteeing quality, the needs for mass customization are clear. A method for designing this type of housing is proposed based on the use of shape grammar and the insertion of bioclimatic strategies for improving thermal comfort for Fortaleza: shading and ventilation. The goal of this research was to modify the rules of an informal settlement shape grammar in order to improve natural ventilation and minimize solar radiation incidence on the houses. Satisfying results were achieved for the customization and for the adopted thermal comfort criteria. A potential for generation of new houses and refurbishment was confirmed. Furthermore, this design process method can be replicated to other communities with the adoption of different shape grammars and strategies, as the context and local climate are considered.